2013
DOI: 10.1016/j.talanta.2013.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Determination of N,N-dimethyltryptamine in beverages consumed in religious practices by headspace solid-phase microextraction followed by gas chromatography ion trap mass spectrometry

Abstract: A novel analytical approach combining solid-phase microextraction (SPME)/gas chromatography ion trap mass spectrometry (GC-IT-MS) was developed for the detection and quantification N,N-dimethyltryptamine (DMT), a powerful psychoactive indole alkaloid present in a variety of South American indigenous beverages, such as ayahuasca and vinho da jurema. These particular plant products, often used within a religious context, are increasingly consumed throughout the world following an expansion of religious groups an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 11 publications
0
41
0
1
Order By: Relevance
“…Conventional time intensive protocols utilizing chromatographic or hyphenated methods such as HPLC-fluorescence, [36] gas chromatography (GC)-or liquid chromatography-mass spectrometry (LC-MS) have been used to isolate and identify DMT and harmala alkaloids in Ayahuasca. [30,[37][38][39][40][41] harmala. Intensive method development is also needed to optimize chromatographic M a n u s c r i p t 10 separation of the components in the brew, which adds to the overall analysis time.…”
Section: Page 8 Of 35mentioning
confidence: 99%
“…Conventional time intensive protocols utilizing chromatographic or hyphenated methods such as HPLC-fluorescence, [36] gas chromatography (GC)-or liquid chromatography-mass spectrometry (LC-MS) have been used to isolate and identify DMT and harmala alkaloids in Ayahuasca. [30,[37][38][39][40][41] harmala. Intensive method development is also needed to optimize chromatographic M a n u s c r i p t 10 separation of the components in the brew, which adds to the overall analysis time.…”
Section: Page 8 Of 35mentioning
confidence: 99%
“…Ayahuasca is an entheogenic beverage that has been consumed for centuries, originally by South American populations, more specifically, by Amazonian indigenous groups, in spiritual rituals and ceremonies in the hope of obtaining further knowledge and divine invigoration [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The harmine, harmaline, tetrahydroharmine, harmalol, and DMT concentrations in the samples ranged from 0.3 to 36.7 g/L (Figure 1). The increase observed for fractions 17-20 can be explained by the addition of all fractions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) to form the apuro (ayahuasca tea) fractions, which contain significant concentrations of DMT and β-carbolines. It is suggested that the absence of tryptamine alkaloid is related to the complete bioconversion to DMT in plants.…”
Section: Application Of the Methodsmentioning
confidence: 99%
“…Accepted by SG November 21, 2016. 1 Corresponding author's e-mail: sandnavi@ufs.br DOI: 10.5740/jaoacint.16-0337 Samples 1-16 were analyzed directly by the SPE method, whereas samples 17-20 were initially diluted (1:100) due to their viscous characteristics that could clog the filter of the SPE cartridges.…”
Section: Technical Communicationmentioning
confidence: 99%
See 1 more Smart Citation